أثر الداء السكري النمط 2 على ثخانة القرنية المركزية و خلايا بطانة القرنية - درويش, تيم; سليمان, يوسف; سكاف, نوار (Latakia University Journal -Medical Sciences Series, 2019)
Purpose : To study the effect of diabetes type 2 on central corneal thickness and corneal endothelium with respect to duration and glycemic control (level of glycosylated haemoglobin) Methods : The corneal endothelial structure and central corneal thickness (CCT) were investigated in 57 type II diabetic patients (114 eyes) and in 46 nondiabetic patients (92 eyes) aged between 40-60 years. The endothelial structure was examined with non contact specular microscope for cell density (ECD), coefficient of variation of cell area(CV), and percentage of hexagonal cells(EX) and CCT was determined using corneal topography . Blood investigation was done to measure the HbA1c level in diabetics Results : The mean CCT in diabetics was 551.7±38.6μm and in non diabetic was 543.7±34.7μm and the difference between the two groups was not statistically significant (p=0.08).. The CCT was thicker for diabetics with HbA1c >6.5% than those with HbA1c ≤6.5% though the difference was not statistically significant. ECD and EX were decreased and CV was increased in diabetic patients and that was significantly different from nondiabetics. ECD and EX was decreased and CV was increased for diabetics with HbA1c >6.5% than HbA1c <6.5% though the differences was not statistically significant. There were a positive correlation between CCT , CV and the duration of diabetes and a negative correlation between ECD ,EX and the duration of diabetes Conclusion : diabetics have thicker corneas , lower ECD , an increased polymegathism , and a decreased pleomorphism . the duration of diabetes is the factor that affects all of these changes . الهدف: دراسة تأثير الداء السكري النمط 2 على ثخانة القرنية المركزية و خلايا بطانة القرنية و ارتباطها مع مدة الإصابة و ضبط سكر الدم ( مستوى الخضاب الغلوكوزي). الطرائق تم استقصاء بنية بطانة القرنية و ثخانة القرنية المركزية لدى 57 مريض (114 عين) مصاب بالداء السكري النمط 2 و 46 من الشواهد الأصحاء (92 عين) تتراوح أعمارهم بين 40 – 60 سنة . تم فحص بنية بطانة القرنية بواسطة المجهر البراق غير التماسي من أجل تحديد تعداد الخلايا البطانية ، معامل تغاير الحجم و نسبة الخلايا السداسية ، تم فحص ثخانة القرنية المركزية بجهاز طبوغرافيا القرنية، تم فحص عينة دم لقياس مستوى الخضاب الغلوكوزي عند مرضى السكري . النتائج : متوسط ثخانة القرنية المركزية لدى السكريين (551.7±38.6 ميكرون) مقارنة بالشواهد (543.7±34.7 ميكرون) دون أهمية إحصائية ، كانت ثخانة القرنية المركزية أعلى لدى السكريين مع قيمة خضاب غلوكوزي > 6.5% منها لدى غير السكريين مع قيمة خضاب غلوكوزي ≤6.5% رغم أن الفارق غير هام إحصائياً . تعداد الخلايا البطانية و نسبة الخلايا السداسية أقل و معامل تغاير الحجم أعلى عند السكريين مقارنة بالشواهد ( بفارق هام إحصائياً). تعداد الخلايا البطانية و نسبة الخلايا السداسية أقل ومعامل تغاير الحجم أعلى لدى السكريين مع قيمة خضاب غلوكوزي > 6.5% منها لدى غير السكريين مع قيمة خضاب غلوكوزي ≤6.5% . علاقة ارتباط إيجابية بين ثخانة القرنية المركزية و معامل تغاير الحجم مع مدة الإصابة بالسكري ، و علاقة ارتباط سلبية بين تعداد الخلايا البطانية و نسبة الخلايا السداسية مع مدة الإصابة. الخلاصة: إن مرضى السكري لديهم قرنية أكثر ثخانة و تعداد خلايا بطانية أقل و نسبة خلايا سداسية أقل ومعامل تغاير حجم أعلى . إن مدة الإصابة بالداء السكري هي العامل الذي يؤثر على هذه المتغيرات.